Agama PENDIDIKAN BERBASIS MODERASI BERAGAMA: UPAYA MEMBANGUN TOLERANSI DAN HARMONI DALAM KEBERAGAMAN: Pendidikan Dan Moderasi Beragama - Nasib Mardika, I Made (Guna Widya: Jurnal Pendidikan Hindu, 2025)
Religious moderation is a key principle in maintaining harmonious religious life in Indonesia's diverse society. In the context of education, the values ​​of religious moderation must be systematically instilled to foster a tolerant, inclusive, and peace-loving generation. This article discusses the concept of religious moderation-based education, its urgency within the national education system, and strategies for its implementation in schools and universities. The method used is a literature review with a qualitative-descriptive approach. The results of the study indicate that religious moderation education can be integrated into the curriculum, extracurricular activities, and teacher training. Instilling values ​​such as tolerance, anti-violence, patriotism, and respect for differences is the main foundation in developing citizens with moderate character.